2010
DOI: 10.1002/jca.20274
|View full text |Cite
|
Sign up to set email alerts
|

Update on extracorporeal photopheresis in heart and lung transplantation

Abstract: Transplant rejection of solid organs remains a threat to thousands of patients despite modern immunosuppressive regimens. The currently available drugs are associated with severe complications such as hypertension, diabetes mellitus, renal failure, risk of infections, and malignancies among many others and, often enough, still allow episodes of rejection. New and less-toxic immunologic measures are desperately needed to accomplish the desired tolerance to the transplant without the undesirable side effects. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 34 publications
0
29
0
6
Order By: Relevance
“…The Journal of Immunology, 2015, 194: 2569-2577. E xtracorporeal photopheresis (ECP) is an immunomodulatory cellular therapy exhibiting clinical efficacy for attenuation of graft-versus-host disease (1-3) and solid organ transplant rejection (4) and for the treatment of cutaneous (5-7) and noncutaneous T cell lymphomas (8). ECP involves collection of leukocytes by apheresis that are exposed to 8-methoxypsoralen (8-MOP) and UVA light and retransfused into the patient (9).…”
mentioning
confidence: 99%
“…The Journal of Immunology, 2015, 194: 2569-2577. E xtracorporeal photopheresis (ECP) is an immunomodulatory cellular therapy exhibiting clinical efficacy for attenuation of graft-versus-host disease (1-3) and solid organ transplant rejection (4) and for the treatment of cutaneous (5-7) and noncutaneous T cell lymphomas (8). ECP involves collection of leukocytes by apheresis that are exposed to 8-methoxypsoralen (8-MOP) and UVA light and retransfused into the patient (9).…”
mentioning
confidence: 99%
“…A retrospective analysis of 71 patients with severe chronic GVHD demonstrated that patients who had received ECP showed an overall response rate of 61%, and complete responses were observed in 20% of patients (98). ECP therapy has also been reported to provide positive clinical outcomes for the treatment of rejection episodes associated with cardiac and lung transplantation (99). In conclusion, published data demonstrate that patients with conditions characterized by overactive inflammation and dysregulation of T cells can realize significant clinical benefit from ECP treatments.…”
Section: Extracorporeal Photopheresis For the Treatment Of Autoimmunementioning
confidence: 90%
“…ЭФХТ рекомендована Американским обще-ством афереза в качестве одного из основных мето-дов профилактики отторжения трансплантата серд-ца и легких [6].…”
Section: экстракорпоральная фотохимиотерапия при трансплантации солидunclassified